Reserve effect of a small North‐East Atlantic marine protected area (Arrábida, Portugal) on soft‐sediment fish species. Issue 7 (4th April 2021) - Martínez‐Ramírez, Lucas; Priester, C. Robert; Sousa, Inês; Erzini, Karim; Abecasis, David
Abstract: The implementation of marine protected areas (MPAs) has been widely used as a tool to manage and conserve marine resources and services. Yet, to date, the reserve effect is still weakly evaluated, particularly for soft‐sediment habitats. The Arrábida MPA, considered as a biodiversity hotspot, was fully established in 2009 on the west coast of Portugal and is characterized by large expanses of soft‐sediment habitats. This MPA was established to protect biodiversity and to ensure the livelihood of the local small‐scale fisheries community. Beyond before–after‐control–impact (BACI) analyses were carried out on catch data (abundance and biomass) of 351 trammel net sets from experimental fishing campaigns (2007–2019) to study the reserve effect on demersal fish populations. The results show a declining trend in abundance inside and outside the protected area, with significant positive effects only found for undersize commercial species and Solea senegalensis, and a general increase in fish species total length. Despite the lack of any obvious reserve effect, the increase in fish length can be considered as a first sign. Anthropogenic pressures are generalized around the area, and transgressions of the restrictions are frequently observed inside the no‐take zone. These can, among other aspects, delay or prevent the expected reserve effects. Therefore, enforcement and/or modification of the spatial plan must be incentivized to achieve the goals of the MPA.